Internationalisation de la recherche et développement : quelles stratégies des constructeurs automobiles dans l’espace est-européen et méditerranéen ? - Nathalie Rodet-Kroichvili; Stéphane Heim; Raymond Woessner (Revue de la Régulation)
This article intends to understand spatial reorganization of R&D activities of automobile manufacturers within the East-European and Mediterranean area. This work is the result of a pluridisciplinary cooperation between an economist, a geographer and a sociologist. It uses a cartographic analysis to highlight a diversity of research and development (R&D) strategies of automobile manufacturers in this geographic area. A qualitative analysis is then proposed to uncover the nature and evolution of overseas R&D activity. The analysis shows that R&D remains an often centralized activity which can nevertheless come along with a decentralization of R&D downstream stages mainly in order to meet market needs and for cost considerations within this geographic area. However we also observe emerging global oriented R&D units.